Modified subxiphoid approach for surgical resection of a retrosternal goiter - Wang, Renfeng; Li, Jianfeng; Jiang, Jiahao; Ding, Jianyong; Yang, Minghui; Wang, Shuai; Lin, Miao (Frontiers in Surgery, 2022)
Backgrounds: Unilateral Video-Assisted Thorascopic Surgery (VATS) is a traditional minimally invasive transthoracic approach for the surgical resection of a subxiphoid goiter. Recently, the subxiphoid approach was recommended for an anterior mediastinal mass. This study aimed to investigate the feasibility and efficacy of a modified subxiphoid VATS for the resection of a retrosternal goiter as an alternative transthoracic approach. Methods: We retrospectively collected all patients who underwent subxiphoid VATS for the resection of a retrosternal goiter from June 2017 to June 2021 in the Zhongshan Hospital or the Zhongshan Hospital Xiamen branch. Ten patients were found. The patient characteristics, perioperative data, and surgical information were collected and further analyzed. Results: In our study, all 10 patients underwent a thoracoscopic subxiphoid resection of a retrosternal goiter. The mean age was 49.4 years, and all were female. The majority of patients (70%) were asymptomatic. All the patients were assessed by CT imaging before surgery. The mean postoperative hospital stay was 4.9 days. The drainage tube was removed three days after the operation, and the average drainage volume was 73.1ml. Postoperative pain was mild, with an average pain grade of 2.4 (measured on a scale from 0 to 10, with lower scores indicating less pain). There were no conversions or perioperative complications in these 10 patients. Conclusions: Most retrosternal goiters can be completely resected through the modified subxiphoid approach after an adequate preoperative evaluation and careful intraoperative management. This thoracoscopic subxiphoid approach is feasible and safe for retrosternal goiter resection.